The Politics of Death Penalty Against Serious Criminal Cases in The Perspective of The New Justice-Based Criminal Code - Raditya Nugraha; A Absori (Universitas Muhammadiyah Surakarta, 2025)
The death penalty is the most severe disciplinary measure in the Indonesian criminal law system. From a theoretical point of view, the use of the death penalty in politics is in line with the idea of using criminal law as a last resort to solve society's problems related to crime. Legal research is a methodical and analytical scientific endeavor that involves the study of a particular legal problem. Therefore, the researcher applies a mixed approach method, namely doctrinal or normative juridical research with a statutory and conceptual approach and empirical juridical (non-doctrinal). Criminal politics, often known as criminal policy, refers to a strategic and logical approach that aims to overcome and reduce crime. The political ideals of the death penalty law include principles that guide the formulation and implementation of policies related to the death penalty. The formulation of criminal law policy throughout the legislative process is a crucial and strategic stage in overall law enforcement planning. The core objective of the application of penalties in the forthcoming National Draft Criminal Code Law is to implement a comprehensive approach that is essential to addressing the consequences of illegal behavior. The Political Law of Death Penalty in the New Criminal Code does not only aim to impose severe punishment but also to be a middle way of practicing the values of Pancasila because it seeks to balance the interests of individuals and society who are pro-contra with the death penalty. Concept of Death Penalty in the New Criminal Code Based on Justice Death penalty is made as a special punishment in the reformation of criminal law and is intended to be used as a last resort to restore goodness to society.